Quantum cryptanalysis of lightweight block cipher Piccolo - Xiaoni DU; Xiangyu WANG; Lifang LIANG; Kaibin LI (Tongxin xuebao)
By taking the characteristics of the structure of Piccolo algorithm RP permutation into consideration, a 3-round quantum distinguisher was proposed.Based on Grover meets Simon algorithm, the 6-round of quantum key recovery attack was given.The results show that the key can be recovered 56 bit with the time complexity 2 28 and the occupation of 464 qubit.Moreover, if attack rounds r＞6，the time complexity is 2 28+16(r-6), which is 1 2 68 of Grover quantum brute-force search.The time complexity of the proposed attack method is significantly reduced compared with Grover search and is also better than that of traditional cryptanalysis, which lays a foundation for the subsequent research on quantum attacks of lightweight block ciphers.